A comparative study on thermal conductivity of multi-walled carbon nanotubes/expanded graphite/graphene enhanced molten nitrate salt: a review - Li, Li; Muhamad, Mat Noor; Kadirgama, Kumaran (Springer Nature, 2024)
This review presents a comprehensive comparative study on the thermal conductivity enhancement of molten nitrate salt when integrated with multi-walled carbon nanotubes (MWCNTS), expanded graphite, and graphene. Thermal conductivity is a crucial parameter in thermal energy storage systems and enhancing it can significantly improve the efficiency of such systems. The paper discusses the individual and synergistic effects of MNCNTS, Expanded graphite, and graphene on the thermal conductivity of Molten nitrate salt. The introduction provides a background on the importance of thermal conductivity in energy storage applications and the rationale behind using MNCNTS, expanded graphite, and graphene. The review then delves into detailed analyses of how each additive—MNCNTS, expanded graphite, and graphene—affects the thermal conductivity of Molten nitrate salt. MNCNTS are highlighted for their high thermal conductivity and structural stability, expanded graphite for its phase change properties and latent heat capacity, and graphene for its superior thermal properties and large surface area. Comparative results are discussed, showcasing the performance of each composite and identifying the most effective combinations. The paper summarizes the key findings, indicating that the hybrid incorporation of these materials can lead to significant improvements in thermal conductivity, thereby enhancing the overall performance of thermal energy storage systems.